CO2-C3H8 cascade refrigeration-heat pump system: Heat exchanger inventory optimization and its numerical verification - Bhattacharyya S.; Mukhopadhyay S.; Sarkar J. (My University, 2025)
This article presents an analytical study on the performance of a cascade refrigeration-heat pump system based on a model incorporating both internal and external irreversibilities. It further explores the optimum allocation of heat exchanger inventories in cascade refrigeration cycles for the maximization of performance and minimization of system cost. In a novel attempt, a CO2-propane cascade system, lately showing good promise as a future solution, has been numerically simulated comprehensively incorporating precision property routines for the working fluids and this numerical model subsequently has been employed for validation of the proposed analytical model. It has been established that the total system heat exchanger inventory should be optimally divided in the ratio of a factor K between the gas cooler and the evaporator heat exchangers for maximal system output and minimal mechanical power requirement for a specified total heat exchanger inventory. It can also be construed that a similar allocation is recommended for minimization of total heat exchanger inventory with specified total system output. A strong assertion of all the analytical model results has been exhibited through a completely independent numerical system simulation. © 2008 Elsevier Ltd and IIR.